Mastering Adobe Premiere Pro CS6. - Ekert, Paul (Packt Pub., 2013)
Designed to be practical and engaging, Mastering Adobe Premiere Pro CS6 is a project-based book to help you truly augment your skills and become a film editing hotshot. If you're just starting out or even migrating from existing video editing software, then this book is for you. With rapid progression through practical examples constructed to be both engaging and useful, Mastering Adobe Premiere Pro CS6 is ideal for learning the sometimes complex workflows of this powerful application.